The Quality Of Public Services In The Context Of Managing Identity Cards (KTP) And Family Cards (KK) In Ampeldento Village, Karangploso District, Malang Regency - Dedi Susanto; David Kasidi; Fahruddin Angga Pradana (Publikasi Indonesia, 2023)
Ampeldento Village is one of the hamlets in Karangploso District, Malang Regency which provides public services in the aspect of population administration. Public services for aspects of population administration in Ampeldento Hamlet, Karangploso District include making Family Cards (KK), Electronic Community Characteristics Cards (e-KTP), Temporary Resident Messages (SKTS) and there are recommended services including: making birth certificates, marriage certificates, certificates land, business permit (HO), introduction to SKCK and SIM. Based on the results of research and reviews that have been tested regarding the quality of public services in terms of population administration in Ampeldento Hamlet, it can be concluded that Ampeldento Hamlet has a large area of 8x6m2 for a capacity of 5 service personnel . The service room has service tables, activity tables, 2 sets of Electronic Community Identity Card recording equipment and remote benches intended for residents waiting for services. The Ampeldento Hamlet office does not yet have sufficient service facilities to provide services to residents such as at least a chair in the waiting room, there is no table for writing in the waiting room, data tools do not yet exist. Facilities such as generators are not maximized, so that when the electricity goes out, the service process will also stop everything, which means residents cannot get services. Hamlet Ampeldento in terms of reliability (reliability) in terms of reliability